Implementation of Legal Protection for Children Victims of Sexual Violence in the Family Environment - Syukur, Nasywa Maulidina; Kusumah, Haidan Angga (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study discusses the implementation of legal protection for children victims of sexual violence in the family environment, which is a form of gross violation of children’s rights. Although there have been various regulations such as Law Number 35 of 2014 concerning Child Protection and the Criminal Code, in practice legal protection has not been fully effective. Cultural factors, social pressure, lack of legal assistance, and fear of victims and families often hinder the reporting and enforcement process. This study uses an empirical normative juridical approach to analyze the extent to which legal rules run in the field. The results of the study show that the role of law enforcement officials, child protection institutions, and family support greatly determines the success of protection for victims. Therefore, it is necessary to increase legal education, psychological assistance, and strengthen synergy between legal institutions and the community in preventing and dealing with sexual violence against children in the family